2009
DOI: 10.1111/j.1471-0528.2009.02363.x
|View full text |Cite
|
Sign up to set email alerts
|

A simple tool to measure patient perceptions of operative birth

Abstract: Objective To assess the feasibility and validity of a maternal satisfaction measurement tool, the SaFE study Patient Perception Score (PPS), after operative delivery.Design Cross-sectional survey.Setting A large maternity unit in England.Sample 150 women who had had an operative birth.Methods We recruited women within 24 hours of birth and quantified their satisfaction with two questionnaires: PPS, and the Mackey Childbirth Satisfaction Rating Scale (CSRS; modified).Main Outcome Measures Participation rate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…A woman’s obstetric history, mode of childbirth, and her feelings towards recent childbirth can also affect childbirth satisfaction. For example: being multiparous, preferring a spontaneous vaginal birth and being able to have a spontaneous vaginal birth [15,28] enhances the women’s satisfaction with giving birth. The feelings associated with childbirth itself, due to limited opportunities of exploration in quantitative studies, pose some confounders like the ‘halo effect’ – a positive attitude prevailing due to successfully giving birth – making it difficult to separate childbirth satisfaction from satisfaction with childbirth services [12,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A woman’s obstetric history, mode of childbirth, and her feelings towards recent childbirth can also affect childbirth satisfaction. For example: being multiparous, preferring a spontaneous vaginal birth and being able to have a spontaneous vaginal birth [15,28] enhances the women’s satisfaction with giving birth. The feelings associated with childbirth itself, due to limited opportunities of exploration in quantitative studies, pose some confounders like the ‘halo effect’ – a positive attitude prevailing due to successfully giving birth – making it difficult to separate childbirth satisfaction from satisfaction with childbirth services [12,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A number of national reviews have been completed, with variable results. 8,9 A simple three-part patient perception score has recently been validated for use after instrumental delivery, 10 and this may be sufficiently user-friendly for regular feedback.…”
Section: Which Quality Indicators?mentioning
confidence: 99%
“…Hospitalization becomes an essentially modern life experience, offering specialized technical assistance; the hospital is the safest place to have a child, but it is also the worst place when it comes to the care received by many women and the loss of their autonomy. 19,21 Nevertheless, in a Brazilian study, women identified the doctor as the only professional trained to take care of them during vaginal birth; 21 however, it is important to note that in two international studies conducted in England and Jordan, [25][26] women reported greater satisfaction with the care received when assisted by obstetrical nurses and midwives. [25][26] Recommendations for obstetric care in vaginal birth and caesarean section…”
Section: Negative Perceptions Related To Vaginal Birth and Cesarean Smentioning
confidence: 99%
“…Just like the compliance with the provisions governing the universal rights of man and the principles of the Single Health System, investments towards improving the quality of care in labor and delivery are necessary, as well as the actual implementation of the Program for Humanization of Prenatal Care and Birth in Brazil. [15][16]19,21,26 They also indicated that it is essential to plan and implement appropriate strategies that can help women experience childbirth with lower levels of fear and anxiety, using coping mechanisms to reduce the levels of pain and help them regain a sense of control during childbirth. 25 The importance of the relationship between health professionals and pregnant women has also been highlighted.…”
Section: Negative Perceptions Related To Vaginal Birth and Cesarean Smentioning
confidence: 99%
See 1 more Smart Citation